Perpustakaan penjana generasi bermaklumat - Perpustakaan Tun Seri Lanang ([S.l.] : X-TREME Productions Sdn. BHd., 2002)
Video korporat Perpustakaan Tun Seri Lanang
Copy available in DVD format
VHS format
Keywords: Libraries; Library administration and organization -- Constitution